THE ROLE OF TEACHER LEADERS AS AGENTS OF CHANGE IN IMPLEMENTING THE INDEPENDENT CURRICULUM AT SMAN 4 SOUTH SOLOK - Kurniawati, Novi kurnia; Sarbaitinil, Sarbaitinil; Yatim, Yenita (LPPM Universitas PGRI Sumatera Barat, 2025)
This research is motivated by the implementation of the Independent Curriculum, which emphasizes student-centered learning, alignment with learners’ needs, and greater learning freedom. In practice, however, traditional teaching methods, limited use of technology, and the need for a positive school culture remain challenges. Therefore, the role of Teacher Leaders as agents of change becomes crucial in promoting innovation, collaboration, and quality improvement at Senior High School 4 South Solok.The study aims to describe the role of Teacher Leaders in implementing the Independent Curriculum, particularly in guiding teachers and students to utilize technology. It employs Talcott Parsons’ structural functional theory with the AGIL scheme, which states that every social system must fulfill adaptation, goal attainment, integration, and latency. A descriptive qualitative approach was applied through field research, with purposive sampling involving Teacher Leaders, non-Teacher Leaders, and students. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using Miles and Huberman’s interactive model.Findings reveal that Teacher Leaders serve as facilitators, motivators, initiators, and innovators through several programs. The ICT-Based Learning Competency Development Program helps students learn physics with technology despite limited laboratory facilities. HELING (Healthy and Environmentally Friendly Living) raises environmental awareness while motivating students in chemistry. The Change Initiative introduces innovation into sociology learning using interactive digital applications, while the Positive Culture program builds a safe classroom climate and student responsibility. These initiatives demonstrate that Teacher Leaders not only bring innovation but also engage students and colleagues in collaboration, creating a dynamic, enjoyable, and student-oriented learning atmosphere consistent with the Independent Curriculum. Keyword: Teacher Leaders, Independent Curriculum, agents of change.